BAHASA PEREMPUAN DALAM KOMUNITAS MAHASISWA FKIP UNIVERSITAS TADULAKO PALU - Yunidar Nur (Balai Bahasa Sulawesi Selatan, 2010)
Study of women language uttered by students society at campus conserning the rejection strategy is interesting to be done, on account of student that women as specific classification of society. The research using pragmatic approach and society ethnography aims to describe the women’ laguange of students society in FKIP UNTAD. In comunication, the students used the direct rejection strategy involving direct strategy to the target which is marked by negation marker ‘nyanda’, ‘nda’, and ‘sorry’ whereas the indirect rejection strategy is classified as: a) counter command strategy, b) counter asking strategy, c) including third part strategy, d) disting vishing form and meaning strategy. This research is a quantitative research that applies speech act theory, pragmatic and comunication ethnography. These date were collected by observation, recording and interview. The interaction model is used continuously from the field data collection to analysis. Their analysis procedure were done by four steps activities, they are the data collection, the data reduction, the data presentation and the conclusion of research finding. Abstrak Studi tentang bahasa perempuan dalam komunitas mahasiswa di kampus tentang strategi penolakan menarik dilakukan, sebab mahasiswa khususnya perempuan merupakan komunitas yang tergolong spesifik. Penelitian yang menggunakan pendekatan pragmatik dan etnografi komunikasi ini, bertujuan untuk mendeskripsikan bahasa perempuan dalam komunitas mahasiswa FKIP UNTAD. Dalam berkomunikasi, mahasiswa menggunakan strategi penolakan langsung yang meliputi; strategi langsung pada sasaran yang ditandai dengan pemarkah negasi nyanda’, nda’, nggak, dan sorry sedangkan strategi penolakan tidak langsung diklasifikasikan atas; a) strategi balik memerintah, (b) strategi balik bertanya, (c) strategi melibatkan orang ketiga, dan (d) strategi membedakan bentuk dan makna. Penelitian ini merupakan penelitian kualitatif dengan ancangan teori tindak tutur, pragmatik, dan etnografi komunikasi. Jenis data ini dikumpulkan melalui teknik observasi, perekaman, dan wawancara. Penganalisisan data menggunakan model interaktif yang dilakukan secara berkelanjutan sejak dari pengumpulan data lapangan hingga usai pengolahan. Prosedur analisisnya melalui empat tahap kegiatan, yakni pengumpulan data, pereduksian data, penyajian data, dan penyimpulan temuan penelitian. Study of women language uttered by students society at campus conserning the rejection strategy is interesting to be done, on account of student that women as specific classification of society. The research using pragmatic approach and society ethnography aims to describe the women’ laguange of students society in FKIP UNTAD. In comunication, the students used the direct rejection strategy involving direct strategy to the target which is marked by negation marker ‘nyanda’, ‘nda’, and ‘sorry’ whereas the indirect rejection strategy is classified as: a) counter command strategy, b) counter asking strategy, c) including third part strategy, d) disting vishing form and meaning strategy. This research is a quantitative research that applies speech act theory, pragmatic and comunication ethnography. These date were collected by observation, recording and interview. The interaction model is used continuously from the field data collection to analysis. Their analysis procedure were done by four steps activities, they are the data collection, the data reduction, the data presentation and the conclusion of research finding.